Malem Songolikur: Menyingkap Makna Harga Dibalik Tradisi Lelang Bandeng di Gresik - Rachmi, Nur Habiba; Sawarjuwono, Tjiptohadi (E-Jurnal Akuntansi; Vol 30 No 5 (2020)DO - 10.24843/EJA.2020.v30.i05.p18, 2020)
The purpose of this study is to reveal the determination process and the meaning of prices implemented through the milkfish auction tradition in Gresik. This research is qualitative using an ethnographic approach, data collected through interviews and participant observation. The results showed that the price determination process used the Rohmatan Lil ‘Alamin principle. The researcher found three meanings of the first price, self-esteem; second, the form of reward; third, the form of obedience to the Creator. Prices are not always matched with material or nominal. Price has a different meaning through the perspective of the Gresik’s. Keywords: Milkfish Biding; Fix Cost Price; Etnography.